2002
DOI: 10.1046/j.1365-2222.2002.01420.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of interleukin‐13 in eosinophil accumulation and airway remodelling in a mouse model of chronic asthma

Abstract: These results imply a critical role for IL-13 in accumulation of intraepithelial eosinophils in chronic asthma, as well as in epithelial and subepithelial remodelling. In addition, they suggest that in chronic asthma, IL-13 may be capable of signalling via a pathway that does not involve IL-4Ralpha.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
125
1
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(141 citation statements)
references
References 42 publications
14
125
1
1
Order By: Relevance
“…2), which was consistent with our previous observations in these mice at 18 hours post-exposure (Kumar et al, 2002). Surprisingly, however, there was strong expression of eotaxin both by tracheal epithelial cells and by plasma cells in the lamina propria in these animals (Fig.…”
Section: Eosinophil Recruitment and Eotaxin Expression In Il-13 ؊/؊ Micesupporting
confidence: 92%
“…2), which was consistent with our previous observations in these mice at 18 hours post-exposure (Kumar et al, 2002). Surprisingly, however, there was strong expression of eotaxin both by tracheal epithelial cells and by plasma cells in the lamina propria in these animals (Fig.…”
Section: Eosinophil Recruitment and Eotaxin Expression In Il-13 ؊/؊ Micesupporting
confidence: 92%
“…AHR and subepithelial remodeling have also been shown to develop in N6 IL-13 Ϫ/Ϫ mice in a chronic model of asthma (32). These observations are in contrast to those reported by Walter et al (23), who showed that IL-13 was critical for the development of allergen-induced AHR in N7 IL-13 Ϫ/Ϫ mice.…”
Section: Discussionmentioning
confidence: 55%
“…Human studies reveal an association between severity of remodeling and AHR in asthma (Chetta et al, 1996;Hoshino et al, 1998), as well as a correlation between increasing subepithelial fibrosis and progression from asymptomatic AHR to asthma (Laprise et al, 1999). However, our previous studies using this experimental model suggest that remodeling and development of AHR can be uncoupled in IL-5-deficient animals, which develop significant airway wall remodeling but not AHR , as well as in IL-13-deficient animals, which do not exhibit remodeling but continue to be hyperreactive to methacholine (Kumar et al, 2002a).…”
Section: Foster Et Almentioning
confidence: 81%